“We Never Get Stuck:” A Collaborative Analysis of Change and Coastal Community Subsistence Practices in the Northern Bering and Chukchi Seas, Alaska - Huntington, Henry P.; Raymond-Yakoubian, Julie; Noongwook, George; Naylor, Noah; Harris, Cyrus; Harcharek, Qaiyaan; Adams, Billy (ARCTIC, 2021)
The Indigenous communities of the northern Bering Sea and Chukchi Sea are experiencing extensive social, economic, and technological change. The region’s marine ecosystem is also characterized by a high degree of variability and by rapid change. Residents of eight coastal communities from Savoonga to Utqiaġvik were involved in the Chukchi Coastal Communities Project, which used the results of a literature review together with the experiences of the community participants to co-analyze what is known about societal and environmental change in the region and what the communities’ experiences have been in responding to those changes. Some of the observed changes are transient in duration and effect, such as the passage of an individual ship, whereas others, such as the creation of the Red Dog Mine Port Site, persist and may force coastal residents to make lasting changes in their activities. Some responses can use existing knowledge (e.g., hunting bowhead whales in fall as well as spring), whereas others may require learning and experimentation (e.g., harvesting new species such as the Hanasaki crab). Our findings show that the results of a change are more important than the source of the change. They also emphasize the continuing importance of traditional values and practices as well as attitudes conducive to persistence and innovation. Indigenous leadership is an essential component of continued resilience as the ecosystem continues to change. The resilient characteristics of coastal communities and their ability to determine their own responses to change need greater attention to match the research effort directed at understanding the ecosystem. Les collectivités autochtones du nord de la mer de Béring et de la mer des Tchouktches font face à d’importants changements sur les plans social, économique et technologique. L’écosystème marin de la région est également caractérisé par un grand degré de variabilité et de changement rapide. Les habitants de huit collectivités côtières, de Savoonga à Utqiaġvik, ont ...